Cytomegalovirus biology - Tortorella, Domenico (Henry Stewart Talks, 2020)
Introduction to human cytomegalovirus (CMV), Diseases associated with CMV, Therapeutics targeting CMV, Development of CMV vaccines, CMV entry factors, CMV life cycle, CMV latency and reactivation cycle, CMV immune evasion strategies including evasion of NK cells